2014
DOI: 10.1177/1533034614551476
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Clinical and Dosimetric Parameters With Radiographic Lung Injury Following Stereotactic Body Radiotherapy

Abstract: Radiographic changes occur in over half of patients treated with stereotactic body radiotherapy (SBRT) to the lung, correlating histopathologically with injury. We quantified radiographic density changes (ie, fibrosis) at 3, 6, and 12 months and investigated the relationship between these volumes and clinical and dosimetric parameters. The study population consisted of patients treated with SBRT to the lung for stage I primary lung cancers (n = 39) or oligometastatic lesions (n = 17). Fractionation schemes inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The maximum point dose (normalDmax) to nearby critical organs at risk (OAR), such as the esophagus, spinal cord, heart, trachea, and proximal bronchus was compared amongst all patients. Lung toxicity parameters analyzed include the absolute volume of normal lung covered by 50% of the prescription or more (normalV50%), predictive of fibrosis, (23) the mean dose to the normal lung (MLD), the normal lung receiving 5, 10, 20, 27 Gy or more (normalV5Gy,normalV10Gy,normalV20Gy,normalV27Gy, respectively), and contralateral lung receiving at least 5 or 10 Gy (normalV5GyC,normalV10GyC, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…The maximum point dose (normalDmax) to nearby critical organs at risk (OAR), such as the esophagus, spinal cord, heart, trachea, and proximal bronchus was compared amongst all patients. Lung toxicity parameters analyzed include the absolute volume of normal lung covered by 50% of the prescription or more (normalV50%), predictive of fibrosis, (23) the mean dose to the normal lung (MLD), the normal lung receiving 5, 10, 20, 27 Gy or more (normalV5Gy,normalV10Gy,normalV20Gy,normalV27Gy, respectively), and contralateral lung receiving at least 5 or 10 Gy (normalV5GyC,normalV10GyC, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Patient-related factors such as age, smoking history, tumor size, tumor location, performance score, and gender- and treatment-related factors including chemotherapy regimen and lung dosimetry have been suggested as predictors for the development of RILD [ 25 – 27 ]. In regards to radiographic change, Kishan et al [ 28 ] reported that age, years since quitting smoking, and GOLD (Global Initiative for Chronic Obstructive Lung Disease) score were significantly associated with volumes of radiographic fibrosis following SABR. They found the predominant patterns of fibrosis peaking volumes of fibrosis at 6 and 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…78 Because most cases of radiation fibrosis involve patchy consolidation or ground-glass densities that develop at 3 months posttreatment and continue to evolve over time, reliance on CT alone may be insufficient in discriminating between fibrosis and recurrence. [79][80][81][82] Takeda et al queried follow-up imaging from 50 patients treated with SBRT who had at least 12 months of follow-up imaging, with a median follow-up of 30.4 months. 83 They noted suspicious opacities in 20 patients (40%); only 3 (6%) actually had proven recurrences, and 14 (70% of those with suspicious opacities) did not.…”
Section: Follow-up and Radiation Fibrosismentioning
confidence: 99%
“…82,[85][86][87][88][89][90] Kishan et al recently quantified fibrotic changes at 3, 6, and 12 months in 56 patients treated with SBRT. 82 The predominant kinetic patterns of fibrosis demonstrated peaking fibrotic volumes at 6 and 12 months, and the investigators found that age, years since quitting smoking, and Global Initiative for Chronic Obstructive Lung Disease score were significantly associated with increasing volume of fibrosis. The investigators also found that a variety of dosimetric parameters were associated with increasing volumes of fibrosis.…”
Section: Follow-up and Radiation Fibrosismentioning
confidence: 99%